2002
DOI: 10.1111/1467-9280.00446
|View full text |Cite
|
Sign up to set email alerts
|

Expertise Training with Novel Objects Leads to Left-Lateralized Facelike Electrophysiological Responses

Abstract: Scalp event-related potentials (ERPs) in humans indicate that face and object processing differ approximately 170 ms following stimulus presentation, at the point of the N170 occipitotemporal component. The N170 is delayed and enhanced to inverted faces but not to inverted objects. We tested whether this inversion effect reflects early mechanisms exclusive to faces or whether it generalizes to other stimuli as a function of visual expertise. ERPs to upright and inverted faces and novel objects (Greebles) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
202
2
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(227 citation statements)
references
References 28 publications
19
202
2
4
Order By: Relevance
“…However, given the current debate about the specificity of the face N170 response (25)(26)(27)(28), our goal was to study the mechanisms involved in processing faces that could be recruited by visual expertise. Furthermore, any effect on N170 in response to objects of expertise under the conditions of concurrent stimulation created here may be difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, given the current debate about the specificity of the face N170 response (25)(26)(27)(28), our goal was to study the mechanisms involved in processing faces that could be recruited by visual expertise. Furthermore, any effect on N170 in response to objects of expertise under the conditions of concurrent stimulation created here may be difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, results from fMRI do not address whether the face-like effects associated with visual expertise for nonface objects occur during initial visual categorization and in the same time frame as those effects elicited by faces, that is, at Ϸ150 ms after stimulus onset (12,21,22). In support of the view that the processing of faces shares similar temporal characteristics with the processing of nonface objects, it has recently been found that the human scalp N170 is larger in response to birds, dogs, or cars in experts within each of these categories (23,24) and that the N170 displays a face-like inversion effect after Ϸ10 h of expertise training with novel nonface objects (25).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, unlike studies of real-world object expertise (1,7), studies with greebles allow participants to be tested before and after training. Several studies have reported that greeble training elicited perceptual (2,14) and neural (15,16) effects similar to the effects characteristic of face processing (but see refs. 17-18 for contrary evidence with greebles and novel nongreeble objects).…”
mentioning
confidence: 91%
“…Moreover, extensive training with novel objects (e.g., greebles) would lead to a stronger N170 response to the trained objects (Rossion, Gauthier, Goffaux, Tarr, & Crommelinck, 2002;Scott, Tanaka, Sheinberg, & Curran, 2006). Given such evidence, the visual word-specific N170 has been argued to reflect the human brain's expertise in reading visual words as a result of years of reading experience.…”
mentioning
confidence: 99%